Proteus syndrome: clinical and radiological findings through a new case report - Barakizou Hager; Khelifi Azza; Ferjani Maryem; Gargah Tahar (SpringerOpen, 2024)
Abstract Background Proteus syndrome (PS) is a complex and uncommon disorder with as its main feature a patchy or mosaic postnatal overgrowth. A high clinical and radiological variability characterizes it. Case presentation We report the case of a 2-year-old boy presenting with lipomas and diagnosed as PS in front of general criteria (sporadic occurrence, progressive course, and mosaic distribution of lesions) and specific criteria (linear epidermal nevus in the chest and asymmetric and overgrowth in the upper limbs) of Biesecker. The course of the disease was marked by a huge overgrowth of arms despite several surgeries. By the age of 10 years, a painful swelling of the right forearm revealed a venous thrombosis on a venous malformation. Conclusions This case report highlights the variability of clinical findings in PS. It also emphasizes the contribution of routine imaging tools for the diagnosis and the follow-up of this rare disease.